Prevalence and Associated Risk Factors of Retinopathy of Prematurity in Preterm Infants: A Cross-Sectional Study - Manisha Kumari; Mohsina Noor Ibrahim; Versha Rani Rai; Zubair Khoso; Roshia Parveen; Ajea Rani (Journal of the Dow University of Health Sciences)
Objective: To determine the prevalence of Retinopathy of Prematurity (ROP) and its associated risk factors in preterm infants at the National Institute of Child Health (NICH), Karachi, Pakistan. Methods: This cross-sectional study was conducted in the neonatal intensive care unit (NICU) department of NICH, Karachi, Pakistan from September 2020 to March 2021. The study included preterm infants with a gestational age under 32 weeks, admitted to the NICU at the NICH, Karachi. ROP was diagnosed by indirect ophthalmoscopy following pupil dilation, performed by a trained ophthalmologist. Risk factors were assessed based on preterm infants' age, gestational age, residence, gender, maternal education, sepsis, respiratory distress syndrome (RDS), anemia, oxygen dependency duration, and mechanical ventilation. Results: Of total 310 preterm infants, the mean age was 5.73 ±1.49 days. There were 184 (59.3%) males and 126 (40.6%) females. ROP was observed in 139 (44.8%) preterm infants. Binary logistic regression indicated significantly increased ROP risk in infants of illiterate mothers (aOR 3.31, 95% CI 1.08 to 10.17, p-value 0.036), those with family income ≤ 45,000 rupees (aOR 3.70, 95% CI 1.40 to 9.76, p-value 0.008), and reduced risk in female infants (aOR 0.12, 95% CI 0.04 to 0.31, p-value <0.001), infants on oxygen ≤ 4 days (aOR 0.04, 95% CI 0.01 to 0.12, p-value <0.001), and NICU stay ≤ 12 days (aOR 0.02, 95% CI 0.01 to 0.08, p-value <0.001). Conclusion: Nearly half of the preterm neonates were affected by ROP, with contributing factors including maternal illiteracy, low family income, prolonged oxygen dependency, and extended NICU stays.